Clear body, clear mind : the effective purification program - Hubbard, L. Ron (La Fayette Ron), 1911-1986 (Bridge Publications, Inc, 2013)
We live in a drug-oriented society. Drugs pervade our world -- from street drugs and medical drugs, to say nothing of the latest "feel-good" pharmaceuticals. Add to that the thousands of toxic substances we are exposed to on a daily basis, including household chemicals, food preservatives and pesticides, and it's easy to see that no one is immune to this crisis. Through the course of his research into the effects of drugs on the human mind, L.Ron Hubbard made a landmark discovery. Namely, that LSD appeared to remain in a person's body long after they stopped taking the drug. This breakthrough explained why someone who had used LSD in the past could suddenly reactivate a "trip" even years later. His further research revealed that many other toxic substances could also remain in the body, producing negative effects for years to come. The question remained: how can you eradicate these harmful drugs and toxins from your body? The answer is the Purification Program developed by Mr. Hubbard. With the inclusion of a precise regimen of vitamins, minerals and oils, we are able to work toward restoring the biochemical balance of the body and make it possible for the body to reconstruct itself from the damage done by drugs and other biochemical substances. - Publisher.